Synthesis and nonlinear optical properties of copolymers of fluoro-containing bisphenol A and chromophores - Shi, Jie Ping; Yang, Hui; Wei, Li; Hu, Hong Wen; Lu, Guo Yuan (Chinese chemical letters, 2011)
A series of new fluoro-containing copolymers have been synthesized by a Mitsunobu reaction with 4,4＇-（hexafluoroisopropylidene） bisphenol A（6FBPA） and the corresponding N,N-dihydroxyethylaminoaryl azo or ring-locked triene compounds, which have high thermal stability and good solubility in organic solvents.The nonlinear optical（NLO） measurements made by Marker fringe method at 1064 nm indicate that the copolymers embedded with the ring-locked triene and azo chromophores exhibit higher macroscopic nonlinear optical coefficient（70.2 pm/V and 26.5-34.6 pm/V,respectively）.Thermal analysis and UV-visible absorption spectra show that the copolymers have good thermal stability（T_d= 264-319℃） and optical transparency （λ_（max）500 nm）.